Faktor-Faktor yang Berhubungan dengan Pencapaian Cakupan Imunisasi Dasar Lengkap pada Bayi di Puskesmas Ba’a Kabupaten Rote Ndao - Santi Batu Sariana Kadja; Serlie K. A. Littik; Yuliana Radja Riwu (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Immunization is an effort to increase a person's immune system to avoid disease. Complete basic immunization coverage in 2018-2022 at the Ba'a Community Health Center experienced a significant decline and tended to be low so that it did not reach the 90% strategic plan target. The purpose of this study was to identify events related to the achievement of complete basic immunization coverage for infants at the Ba'a Community Health Center. The type of research used was quantitative with a cross-sectional study design. The age of the infants in this study ranged from 10-12 months, and the respondents were mothers of infants residing in the Ba'a Community Health Center work area. The sampling technique used purposive sampling, a sample of 72 respondents. The data obtained were analyzed using the chi-square test. The test results show that there is a relationship with a sufficient level of correlation between the variables of knowledge (0.018; r = 0.343), attitude (0.004; r = 0.384), distance (0.010; r = 0.340) and family support (0.026; r = 0.322), with the completeness of basic immunization in infants, while the support of health workers has a very weak level of correlation (0.554; r = 0.118) so that there is insufficient evidence to accept that there is a relationship between the support of health workers and the completeness of basic immunization in infants. It is recommended that the husband/family be willing to accompany the mother to the immunization site and provide motivation for the mother.